HUSBAND'S SUPPORT FOR MATERNAL MENTAL HEALTH POSTPARTUM: DOES THE HUSBAND'S EDUCATION PLAY AN IMPORTANT ROLE? - Tri Wurisastuti; Santi Martini; Siti Masitoh (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The presence and support of the husband play an important role in maintaining the mental health of young mothers after childbirth. where the mother depends on her husband for all decisions and the husband's education aspect may play an important role. The purpose of this research is to prove the influence of husband education on maternal mental health after childbirth. This study used the data cross-sectional of Basic Health Research 2018 with the analysis sample being mothers aged 15-24 years who had just given birth for a maximum of six months and were still married. Maternal mental problems within one month were measured using Self-Reported Questionnaire-20 (SRQ-20), This questionnaire consists of twenty questions with two answer choices; yes and no. A cut-off score of less than six stated to have postpartum mental problems. Multiple logistic regression was used in this analysis. Young postpartum mothers (n=755; 21 + 2.23 years; 37 + 2.31 weeks of pregnancy at birth), of which, There were 66 (8.7%) mothers had general mental problems. The results of the analysis stated that working mothers who have husbands with education below high school have a risk of postpartum mental problems five times (AOR = 5.36; 95% CI 1.398 – 2.552; p =0.014) higher than mothers with husbands educated above high school. Education is still an important part of overcoming health problems in Indonesia. Limiting the minimum age of marriage is also important so that the younger generation focuses on achieving their education, before entering the marriage level.